Recurrent transitional cell carcinoma of the bladder: A mixed nested variant case report and literature review - De Berardinis, Ettore; Busetto, Gian Maria; Giovannone, Riccardo; Antonini, Gabriele; Di Placido, Mariarosaria; Gentile, Vincenzo (Canadian Urological Association Journal, 2012)
Nested variant of urothelial cell carcinoma (NVUC) is a rare histological entity, with about 80 reported cases. It has a deceptively benign appearance with an aspect characterized by confluent small nest or urothelial’s cell tubules. This tumour often resembles inverted papilloma, von Brunn’s nests (VBNs), cystitis cystica, nephrogenic metaplasia and sometimes usual transitional cell cancer. It is very important to be able to distinguish between benign lesions and nested variant bladder cancer because, in spite of its bland morphology, there is evidence that it behaves aggressively.